PENINGKATAN PENGETAHUAN KADER POSYANDU TENTANG CACINGAN DAN PENCEGAHANNYA - Fatihah Wari Nurjanah; Dewi Setyoningsih; Triwahyuniastuti (LPPM ITB AAS Indonesia Surakarta, 2026)
Helminthiasis (worm infection) remains a serious health challenge among toddlers, characterized by clinical symptoms such as decreased appetite, stunted weight gain, a distended abdomen, as well as weakness and pallor. If left untreated, this condition poses a risk of chronic malnutrition and even stunting. Posyandu (Integrated Healthcare Center) cadres play a central role as the frontline of public health education. This community service aims to enhance the knowledge and capacity of Posyandu cadres, empowering them to act as motivators and role models within their communities for independent and sustainable helminthiasis prevention efforts. This activity was conducted through interactive educational sessions focusing on environmental sanitation, personal hygiene, and the dangers of helminthiasis. Following the educational session, the activity proceeded with assisting the cadres in the distribution of anthelmintic drugs (pyrantel pamoate/albendazole), which are to be administered to toddlers in their respective working areas in accordance with health protocols.Through this activity, a significant improvement in the cadres' knowledge scores regarding the helminth life cycle and its prevention is expected. Furthermore, the active involvement of cadres in anthelmintic drug distribution is anticipated to increase the coverage of the deworming program and reduce the prevalence of intestinal infections among toddlers in the community service area. Kata kunci: Peningkatan/Pengetahuan/ Kader Posyandu/Cacingan/Pencegahannya